HUBUNGAN PEMAHAMAN IBU TENTANG PESAN GIZI SEIMBANG DENGAN STATUS GIZI ANAK PRASEKOLAH DI TK IT AULADUNA KOTA BENGKULU - Yuliantini, Emy; Kusdalinah, Kusdalinah; Yuliani, Andhika Putri (PERSATUAN AHLI GIZI INDONESIA, 2015)
ABSTRACTMother's knowledge about balanced nutrition is important, since the role of the mother in the family is as the manager of food service. The quantity and quality of food and beverages consumed in the family level will affect health of all family’s members and finally it will affect communities as well. To keep the body healthy and is protected from chronic diseases or non-communicable diseases (NCDs) related to nutrition, individual diet needs to be improved to nutritionally balanced through consumption. Efforts have been made in monitoring the nutritional status and a set of good diet. This study aimed to explore understanding of mothers about balanced nutrition and nutritional status of preschool children at IT Auladuna kindergarten in Bengkulu City. It was an observational design with cross sectional study, take place at IT Auladuna kindergarten in Bengkulu City. The study population was a preschooler. Sampling was taken using proportional sample size (PPS) of 68 people. Data on maternal knowledge were collected through interviews using questionnaires, Body Weight (BW) and height of children were measured using standarized equipments. Based on the chi-square test results showed that mother’s knowledge about tumpeng/cone balanced nutrition had a significant relationship to nutritional status of preschooler (p ≤ 0.05), whereas knowledge about My Plate is not associated with nutritional status of preschooler. This study concluded that only the knowledge of mothers about cone-balanced nutrition was significant to nutritional status of their preschool children at IT Auladuna kindergarten in Bengkulu City.Keywords: nutritional status, knowledge of mother, balanced nutrition, preschool childrenABSTRAKPengetahuan ibu tentang gizi seimbang sangatlah penting, mengingat peran ibu dalam keluarga sebagai pengelola makanan. Ibu yang tidak tahu gizi makanan, akan menghidangkan makanan yang tidak seimbang gizinya. Agar tubuh tetap sehat dan terhindar dari berbagai penyakit kronis atau penyakit tidak menular (PTM) terkait gizi, maka pola makan masyarakat perlu diarahkan ke konsumsi gizi seimbang. Upaya yang dilakukan dalam memantau status gizi dengan mengatur pola makan yang baik. Penelitian ini bertujuan mengetahui pemahaman ibu tentang tumpeng gizi seimbang dengan status gizi anak prasekolah di TK IT Auladuna Kota Bengkulu. Desain penelitian ini adalah observasional dengan metode cross sectional di TK IT Auladuna Kota Bengkulu. Populasi penelitian adalah anak prasekolah. Pengambilan sampel dilakukan dengan cara proporsional sampel sebanyak 68 orang. Data tentang pengetahuan ibu dilakukan dengan wawancara menggunakan kuesioner dan data pengukuran BB dan TB anak dilakukan dengan melakukan penimbangan dan pengukuran menggunakan alat terstandar. Berdasarkan uji chi-square diperoleh hasil bahwa hanya pengetahuan tentang tumpeng gizi seimbang ada hubungan nyata dengan status gizi (p 0,05), namun tidak pada pengetahuan tentang piring makanku. Pengetahuan tentang gizi seimbang perlu ditingkatkan pada semua kelompok masyarakat khususnya pada ibu yang mempunyai anak prasekolah.